Stratigraphic and igneous relationships west of Yass, eastern Lachlan Orogen, southeastern Australia: subsurface structure related to caldera collapse?. Issue 7 (3rd October 2019) - Fergusson, C. L.; Chenhall, B. E.; Guy, S.; Jones, B. G.; Solomons, M.; Colquhoun, G. P.
Abstract: Volcanic rocks are widespread in middle Silurian to Lower Devonian rocks of the Lachlan Orogen in southeastern Australia. In the Yass–Canberra region, the Silurian succession consists of two S-type dominantly ignimbrite suites with the lower Hawkins/Goobarragandra and upper Laidlaw volcanics separated and overlain by clastic-carbonate intervals, and unconformably overlain by Lower Devonian silicic volcanic rocks. In the Talmo area, 30 km west of Yass, the Goobarragandra Volcanics are overlain by a clastic-carbonate succession of the Talmo Formation, which has a partly faulted boundary with the Lower Devonian Mountain Creek Volcanics containing rheomorphic welded ignimbrites. The contact of the Mountain Creek Volcanics and the Talmo Formation coincides with the margin of a prominent ovoid gravity low. Dip patterns in the Talmo Formation indicate two orientation domains divided by a northwest-trending faulted boundary. The domain to the southwest consists of gently northeast-dipping interbedded limestone and mudstone whereas the domain to the northeast has steep to moderate dips to the south and southeast with interbedded limestone and mudstone overlain by massive mudstone and quartz-rich turbidites. These contrasting domains are interpreted as a result of subsurface differential downsag, possibly a caldera, accommodated by downwarping in the adjacent Talmo Formation and accompanied by movements across a northwest-trending fault and potential ring faults.